Uncovering hidden diversity in Phaseolinae (Leguminosae): the recircumscription of Phaseolus obliquifolius and its taxonomic placement in Ancistrotropis - Santos, Felipe Da Silva; Ribeiro, Carolina Lima; Snak, Cristiane; Delgado-Salinas, Alfonso; Queiroz, Luciano Paganucci De (Phytotaxa, 2025)
Phaseolinae is a monophyletic subtribe, morphologically recognised by the bearded style enclosing the stigma. Despite recent advances in generic delimitation based on phylogenetic studies, the placement of some taxa remains uncertain. Based on detailed morphological analyses and a revision of herbarium material, we reassessed the taxonomic position of Phaseolus obliquifolius, historically synonymised under Condylostylis candida. Our data support its placement in Ancistrotropis, a Neotropical genus segregated from Vigna based on diagnostic characteristics. We formally propose the new combination A. obliquifolia, accompanied by comparisons with similar taxa, a morphological description, distribution data, and a preliminary conservation status assessment.